Early Written Books Of The Hanafi School (Texas Journal of Multidisciplinary Studies, 2024)
The jurists of the Hanafi madhhab differ from other madhhabs in interpreting the book. From the time of Abu Hanifa until today, many works have been created in the Hanafi school. At that time, the "Original" books written by Imam Muhammad are considered the first published works within the sect. In this article, we covered this topic in detail!